The immune gene expression profile of sterile and fertile Atlantic salmon (Salmo salar L.) during smoltification and post transportation stress - A comparative overview - Sævareid, Katarina (UiT The Arctic University of Norway, 2022)
The escape of farmed salmon may result in unwanted interbreeding with wild salmon populations. The development of a sterile salmon can prevent the negative effect of unwanted genetic introgression as well as provide the industry with solutions to drawbacks associated with sexual maturation. A sterile fish will also improve the competitive strength of the 6 Norwegian breeding companies as the fish delivered cannot be used for breeding stocks. Currently the only sterile fish commercially available is the triploid salmon which is not performing optimal as it is sensitive to suboptimal environments and prone to deformities and is at present banned by the authorities for use in Norwegian aquaculture. Therefore, it is necessary to find new methods to produce sterile fish for commercial use without compromising fish welfare. Through the project “Salmosterile” at Nofima AS there has been developed a new method for sterilization based on preventing the formation of the germ cell line during early development. Removal of the maternally provided ‘Dead end’, which is a critical factor for formation and maintenance of the germ cell line, by antisense oligonucleotides result in a germ cell free and sterile fish. Before this sterilization method can be transferred to large scale commercial production of sterile salmon, it is important that the effect of germ cell loss is evaluated in consideration of the fish’s different physiological systems. It is, amongst other systems, important to ensure that the immune systems of the new sterile fish are robust and can handle stress equivalent to that of the fertile fish. To evaluate parts of the immune system and endocrine regulation during known challenging physiologically processes, sterile and fertile fish was subjected/exposed to a protocol for photoperiod induced smoltification followed by a simulated smolt transport. During the study, expression of 8 gene markers of innate immune response and have been investigated by qPCR: IL1ß, CATH-2, HSP70, sIgM, TCR1α, IL10, IFN-γ, TNF1α, and ...